DETECTION OF SOFT WHEAT RESISTANCE DONORS TO YELLOW RUST (Experimental biology, 2016)
The results of studying of 70 varieties and lines of soft wheat resistance to yellow rust are presented in this article. During researches 31 samples of winter wheat (44,3% of number studied) showed horizontal resistance, and 29 varieties and lines (41,4%) – race specific resistance to diseaseAmong them PP 530, LC909, Saskia, Vlasta, Occitan, Beavborg, Ada, Saihun, Expres and Taz varieties showed both field and race specific resistance to pathogen. Besides the perspective lines 665N797-6, 686N25-9, 694N436, 837N292-4, E-99, E-574, E-578, E-782 and E-789 are presented the great interest on resistance to disease. Molecular screening showed that 3 samples of winter wheat have Yr5 gene resistance, 7 samples – Yr10 gene resistance, 6 samples – Yr15 gene resistance.
Keywords: wheat; yellow rust; Yr-genes; molecular markers.